Rare case of midgut volvulus with malrotation in an elderly patient - Raleng, Mezhuneituo; Pore, Anant Prakash; Katheria, Vickey; Khamrang, Worshim; Wungramthing, R. S. (International Surgery Journal, 2019)
A 70 year old male who was under treatment for lymphoma, presented with a 2 day old history of not passing stool, flatus, associated with vomiting and abdominal distension. Patient was diagnosed as subacute intestinal obstruction and put on conservative management. However since his condition worsen exploratory laparotomy was performed. On laparotomy a midgut volvulus was detected and subsequently de-rotation of small gut was done. Through this paper we would like to stress out the difficulties in diagnosis and the challenges that we faced.